Multibeam bathymetry processed data (Atlas Hydrosweep DS 2 echo sounder entire dataset) of RV POLARSTERN during cruise ARK-XIX/4a (PS64), Greenland Sea, Arctic Ocean - Hans Werner Schenke; Steffen Gauger; Andreas Winkler; Birger Reese; Simon Dreutter; Boris Dorschel (PANGAEA, 2025)
Multibeam data were collected during RV Polarstern cruise ARK-XIX/4a (2003-08-10 to 2003-09-20). Multibeam sonar system was Atlas Hydrographic Hydrosweep DS 2 multibeam echo sounder. Data are processed with Caris HIPS, including sound velocity correction by cross fan calibration and World Ocean Atlas 18 (https://www.ncei.noaa.gov/archive/accession/NCEI-WOA18), tidal correction with TPXO9_atlas_v5 (https://www.tpxo.net/global/tpxo9-atlas), and manual cleaning. The soundings are combined in daily files, the format is XYZ ASCII (<Lon> <Lat> <Depth in meters, positive up, relative to mean sea level>). Additional grids have been computed with depth dependent cell size to visualize the data. These grids are not meant for scientific analysis or navigation, but for overview purposes only.